A critical evaluation of EU maritime policy (1957, 1986–2010). (1st January 2012) - Goulielmos, Alexander M.; Lun, Y.H. Venus
We stress the basic pillars of EU's Maritime Policy: 'competition, quality ships, and short sea shipping'. EU expressed its dissatisfaction with IMO, destined, by shipping community, to safeguard safety. This emerged after 1985, when national flags created parallel registries. The common maritime policy was absent from 1957 till 1986, due to the unanimity principle, as argued. The qualified majority adopted, but unfortunately, for decisions in maritime matters, it remained as it was when the Union was established. This paper found it fair to propose a new allocation of votes among MS, when maritime matters are decided, based on fleet owned under national flag. Great achievement for the Union in 1986 was the four regulations, 4055–4058, reinforcing competition and recognised as the foundation of EU Maritime Policy. Flagging-out during the crisis of 1981–1987 remained. In 1989, EU proposed the so called 'positive measures', one of which was to establish an EU Register of ships, which failed twice EU Maritime Policy was driven by marine accidents and quality shipping there after to this day.